2020
DOI: 10.1186/s12887-020-02435-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum 25-Hydroxyvitamin D with Vitamin D intervention and outdoor activity among children in North China: an observational study

Abstract: Background Living at high latitudes is one of the risk factors for vitamin D deficiency in children. However, evidence on vitamin D improvement for this pediatric population to date is limited. This study aims at evaluating the association of different vitamin D intervention methods and outdoor activity on the vitamin D status of children in North China. Methods In this observational study, a total of 55,925 children aged 1 month to 18 years old we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…In a retrospective study conducted by Xuguang Zhang et al, 55,925 children’s serum samples were collected to study the serum vitD levels. They found that the overall rate of hypovitaminosis D of 65.60% [ 25 ] was similar to our study results. We further analyzed the correlation between BMD and nutritional status.…”
Section: Discussionsupporting
confidence: 91%
“…In a retrospective study conducted by Xuguang Zhang et al, 55,925 children’s serum samples were collected to study the serum vitD levels. They found that the overall rate of hypovitaminosis D of 65.60% [ 25 ] was similar to our study results. We further analyzed the correlation between BMD and nutritional status.…”
Section: Discussionsupporting
confidence: 91%
“…Female gender, older age, obesity, limited dietary dairy intake, limited sun exposure, geographic region, and seasonal period have been reported as risk factors for vitamin D deficiency [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Similarly, our study found that female gender, obesity, lack of outdoor activities, and lower dietary dairy intake were risk factors for vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that assessed the vitamin D status of healthy children in Thailand reported that the prevalence of vitamin D deficiency (25(OH)D < 20 ng/mL) was 19.5–33.4% [ 8 , 9 , 10 , 11 ]. Female gender, older age, obesity, limited dietary dairy intake, limited sun exposure, geographic region, and seasonal period have been reported as risk factors for vitamin D deficiency [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In addition to these potential risks, CCSs have increased risks for vitamin D deficiency, including restrictions on outdoor activities and exposure to steroids, chemotherapy, and/or radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to use supplements of Vit A, D, and E for these children, especially in the high‐altitude areas. 37 …”
Section: Discussionmentioning
confidence: 99%
“…The diet of children from this region is mainly composed of mantou, Zanba, buttered tea, highland barley, and yogurt, and they also occasionally eat beef and mutton but rarely vegetables, fruit, seafood, pork, or poultry. Therefore, it is very important to use supplements of Vit A, D, and E for these children, especially in the high‐altitude areas 37 …”
Section: Discussionmentioning
confidence: 99%